Polityka regionalna Unii Europejskiej po przyjęciu nowych członków - potrzeby i kierunki ewolucji - Rynio, Dorota (The regional policy of the European Union after accessing of new members - needs and directions of evolution, 2006)
Ten new members enlarging process of the European Union causes the need of changes in the way of financing ofequate differences on a level of regional development and in meaning of regional policy. The European Union is creating a new model of regional policy. The direction of changes is a result of negotiations among member countries and effect of market economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 72-78